DAMPAK KEBIJAKAN PEMERINTAH TERHADAP DINAMIKA HUBUNGAN INDUSTRIAL DAN AKTIVITAS SERIKAT PEKERJA: Kebijakan Pemerintah dan Implementasinya, Dampak Kebijakan Pemerintah Terhadap Dinamika Hubungan Industrial dan Aktivitas Serikat pekerja - Rayhan Sabrina; Heru Ilham Patria (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2024)
This research examines the impact of government policies on the dynamics of industrial relations and trade union activities in Indonesia. Using a qualitative approach, this study describes how these policies affect the interactions between employers, workers, and trade unions, as well as the role of trade unions in advocating for their members' rights. The results show that changes in government policies, particularly related to the Job Creation Law, have altered the legal framework of labor relations with various implications for the stability of industrial relations and workers' welfare. The Pancasila Industrial Relations approach serves as the main foundation in achieving harmony and justice in industrial relations in Indonesia, following the values of Pancasila that promote social justice, democracy, and shared prosperity.